Ubiquitous [Na(+)](i)/[K(+)](i)-Sensitive Transcriptome in Mammalian Cells: Evidence for Ca(2+) (i)-Independent Excitation-Transcription Coupling - Koltsova, Svetlana V. (Public Library of Science, 2012)
Stimulus-dependent elevation of intracellular Ca(2+) ([Ca(2+)](i)) affects the expression of numerous genes – a phenomenon known as excitation-transcription coupling. Recently, we found that increases in [Na(+)](i) trigger c-Fos expression via a novel Ca(2+) (i)-independent pathway. In the present study, we identified ubiquitous and tissue-specific [Na(+)](i)/[K(+)](i)-sensitive transcriptomes by comparative analysis of differentially expressed genes in vascular smooth muscle cells from rat aorta (RVSMC), the human adenocarcinoma cell line HeLa, and human umbilical vein endothelial cells (HUVEC). To augment [Na(+)](i) and reduce [K(+)](i), cells were treated for 3 hrs with the Na(+),K(+)-ATPase inhibitor ouabain or placed for the same time in the K(+)-free medium. Employing Affymetrix-based technology, we detected changes in expression levels of 684, 737 and 1839 transcripts in HeLa, HUVEC and RVSMC, respectively, that were highly correlated between two treatments (p<0.0001; R(2)>0.62). Among these Na(+) (i)/K(+) (i)-sensitive genes, 80 transcripts were common for all three types of cells. To establish if changes in gene expression are dependent on increases in [Ca(2+)](i), we performed identical experiments in Ca(2+)-free media supplemented with extracellular and intracellular Ca(2+) chelators. Surprisingly, this procedure elevated rather than decreased the number of ubiquitous and cell-type specific Na(+) (i)/K(+) (i)-sensitive genes. Among the ubiquitous Na(+) (i)/K(+) (i)-sensitive genes whose expression was regulated independently of the presence of Ca(2+) chelators by more than 3-fold, we discovered several transcription factors (Fos, Jun, Hes1, Nfkbia), interleukin-6, protein phosphatase 1 regulatory subunit, dual specificity phosphatase (Dusp8), prostaglandin-endoperoxide synthase 2, cyclin L1, whereas expression of metallopeptidase Adamts1, adrenomedulin, Dups1, Dusp10 and Dusp16 was detected exclusively in Ca(2+)-depleted cells. Overall, our findings indicate that Ca(2+) (i)-independent mechanisms of excitation-transcription coupling are involved in transcriptomic alterations triggered by elevation of the [Na(+)](i)/[K(+)](i) ratio. There results likely have profound implications for normal and pathological regulation of mammalian cells, including sustained excitation of neuronal cells, intensive exercise and ischemia-triggered disorders.